Ops i think i need to be boiled in hot oil that.

I have already these equations : (1) 1-2x+x^2 + 9-6y+y^2 + 1-2z+z^2 = r^2

**<--- I didn't check if you have done these calculations correctly**
(2) 9-6x+x^2 + 4-4y+y^2 + 1-2z+z^2 = r^2

(3) 25-10x+x^2 + 4-4y+y^2 + 1-2z+z^2 = r^2

(4) 100-20x+x^2 + 1-2y+y^2 + 4-4z+z^2 = r^2

So i subtract (1) with (2) , (1) with (3) and (1) with (4).

**<--- at the RHS of the equations you have r^2 - r^2 = 0**
And i will have: (5) -3+4x-2y

(6) -34+8x-2y+6z

(7) -94+18x-4y+2z

Am i doing it right?